To investigate outcomes in endoscopic management of early oesophageal adenocarcinoma in Barrett oesophagus: experience at three Australian tertiary centres. Issue 4 (13th April 2022) - Pateria, Puraskar; Chong, Andre; Muwanwella, Niroshan; Siah, Chiang; Kumarasinghe, Priyanthi; Raftopoulos, Spiro
Abstract: Background: Barrett oesophagus is a known precursor of oesophageal adenocarcinoma (EAC). Early EAC includes T1a (invasion into mucosa) and T1b (invasion into submucosa but not muscularis propria). Endoscopic mucosal resection (EMR) provides accurate histological staging and definitive treatment for early EAC. Post EMR, the remaining Barrett is eradicated with radiofrequency ablation (RFA). However, there is a paucity of long‐term Australian data. Aim: To investigate the efficacy and long‐term outcomes of EMR and RFA in the management of early EAC. Methods: Retrospective analysis of patients early EAC treated endoscopically at three Western Australian tertiary centres, with at least 12‐months follow up, over the past 10 years. Results: Sixty‐seven patients with early EAC (61 T1a and 6 T1b) were treated with EMR. Complete Barrett eradication was done by EMR in 31 of 67 patients whereas 36/67 patients underwent RFA for residual Barrett. EMR changed pinch biopsy histology from HGD ( n = 33), HGD suspicious for IMC ( n = 5) and LGD ( n = 1) to early EAC in 58.2% ( n = 39) patients. During a mean follow up of 37.2 months (interquartile range: 20, 56), complete remission of dysplasia and intestinal metaplasia was seen in 97% ( n = 65) and 89.5% ( n = 60) patients. One patient with T1b EAC underwent oesophagectomy. No cases developed metachronous EAC, progression to invasive adenocarcinoma or development of nodal/distant metastasis. Complications were endoscopically treated haematemesis ( n = 1) and strictures ( n = 16) requiring dilatations. Three patients died due to causes unrelated to IMC. Conclusion: EMR in conjunction with RFA is an effective and safe management for early EAC. EMR provides accurate staging and has low complication rates.